PUNISHMENTS OF BRAHMIN WOMEN MARRIAGE IN BALI (IN THE PERSPECTIVE OF HINDU VALUES) - Ida Ayu Sadnyini (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2016)
ABSTRACT Brahmin women marriage to men of different castes in Bali is called intermarriage in terms of customary law, commonly is called asupundung. Punishments for such marriages still exist among people, especially patiwangi ceremonies and other social punishments. This study is conducted based on that issue. The research problems are how do punishmentsof Brahmin women marriage to men of different castes apply? How are marriage punishments in the perspective of Hindu values? The method used is empirical legal research using primary and secondary data which then are analyzed using legal theory, principles and teachings of Hinduism in qualitative descriptive and finally arguments are provided. Punishments for this marriage include: killed by jumping into the fire, drowned in a sea with a stone tied around legs, isolated, downgrading, not allowed to go home, refined language. These punishments in Hindu perspective are contrary to the teachings of Tri Hita Karana, Tri Kaya Parisudha, Vasudaiva, Kutumbakam, Tat WamAsi, Manusapada, Ardhanareswari, Akhroda, Ahimsa.